IMPLEMENTATION OF STEAM-BASED PROBLEM BASED LEARNING (PBL) LEARNING MODEL TO IMPROVE STUDENTS' CRITICAL THINKING ABILITIES - Lena Rosdiana Pangaribuan; Simon Maruli Panjaitan; Muda Sakti Raja Sihite (Jurnal Manajemen Pendidikan, 2026)
This classroom action research aims to improve students’ critical thinking skills through the implementation of the STEAM-based Problem Based Learning (PBL) model at SMA Negeri 15 Medan. The research subjects were 32 eleventh-grade students. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research instruments included observation sheets, critical thinking skill tests, and documentation. The results show that the implementation of STEAM-based PBL significantly improved students’ critical thinking skills. In the pre-action stage, the percentage of students achieving mastery in critical thinking was only 37.5%. After the first cycle, it increased to 65.6%, and by the second cycle, it further increased to 87.5%. This improvement was supported by more active and collaborative learning activities, as well as students’ better ability to analyze problems systematically through the STEAM approach. Therefore, the STEAM-based PBL model is effective in enhancing students' critical thinking skills in the learning process at SMA Negeri 15 Medan.